Investigation of Wind Characteristics and Cooling Effects of Crushed-Rock Embankment with Different Pavement Widths in Permafrost Region - Hongting Zhao; Xiaolin Li; Xiaopeng Wu (Atmosphere, 2023)
A crushed-rock embankment (CRE) with a high porous crushed-rock layer (CRL) can effectively cool the underlying permafrost through natural ventilation within the layer. However, in addition to the ambient conditions, the ventilation efficiency of the CRL and its cooling effect are significantly affected by the pavement width. In this study, the local wind flow around an embankment section was first analyzed based on field monitoring data. Then, considering climate warming, a 2-D coupled model of heat and mass transfer was established to investigate the wind characteristics and the cooling effects of the CRE with different pavement widths. The results showed that the pavement width exerted considerable impacts on the wind characteristics and cooling effects of the CRE. These impacts were evaluated via variations in the wind speed, the permafrost table, and the soil temperatures. An increase in pavement width can lower the wind speed within the CRL, which is adverse to the long-term thermal regimes of the embankment and the underlying permafrost. In addition, due to differential wind flows around the embankments, an asymmetric distribution of the soil temperatures beneath the windward and leeward sides of the embankments existed. Overall, it is hoped that the results of this study can provide informative references for the Qinghai–Tibet expressway that is constructed in permafrost regions.